Analisis Bibliometrik Green Human Practices terhadap Keberlanjutan Lingkungan pada Industri Perhotelan - Asfiah, Nurul; Arifiani, Ratya Shafira; Rumijati, Aniek (Jurnal Manajerial, 2024)
Background – Attention to environmental issues has become a seriously focus in various companies today, especially in the management of management functions. Awareness of environmental issues has prompted companies to change their concepts and take initiatives to implement sustainable practices. In this context, Human Resource Management plays a crucial role in maintaining the sustainability of an organization. This research aims to explore how the role of green human resource practices influences environmental sustainability in the hospitality industry. Aim – This research aims to explore how the role of green human resource practices influences environmental sustainability in the hospitality industry. The hospitality industry is one of the sectors that has a significant impact on the environment. Design / methodology / approach – The study is a qualitative approach and it was conducted in 2023 by retrieval on Scopus databased via scopus.com., with the results of collecting 611 articles, which were identified in 2018 – 2023. The data were analyzed descriptively and processed by VOSViewer software with a bibliometric approach to understand trend of the development of research for the future. Findings – Research on green human resource management practices has been conducted in the last five years, but this topic is more frequently explored in 2023. In the citation presentation, it is evident that Sustainability Switzerland and the Journal of Cleaner Production are more commonly used for publications on the theme of GHRM Practices. Conclusion – Research on green human resource management practices has been conducted for the past five years, and was more frequently conducted in 2023, as indicated by the number of citations in Sustainability Switzerland and the Journal of Cleaner Production with the theme of green human resource management practices with a high number of publications. Research implication – The number of keywords that are connected to other topics, makes a reference for further researchers to develop research with other approaches, such as quantitative, by distributing questionnaires to several companies, one of which is the hotel industry. Limitations – Companies need to pay attention seriously to the environment, which was currently a global concern. They need to improve environmentally friendly behavior in real terms through GHRM policies and practices, and also research support from academics.